Students' assessment on dialogue and argumentation in society and school Procjena studenata o dijalogu i argumentiranju u društvu i školi - Diković, Marina (2021)
The purpose of this study was to contribute to the model of preparing students for active argumentation in democratic societies and emphasize the teacher"s role in classroom discussions /1/. As many as 245 university students reflected upon the statements in the Questionnaire about dialogue and argumentation. The research objective was to investigate the opinion of students – future teachers about argumentation. Results show that students evaluate in a more positive way the areas of argumentation at school from the aspect of the relationship among school stakeholders, with the relationship between pupils as the mostly evaluated; those who have the highest level of knowledge on the concept of argumentation evaluate more positively that engaging in different society activities develops cohesion, dialogue and argumentation. Students with better assessment on the important teachers' characteristics for argumentation show higher understanding for the encouragement of school activities which contribute to the development of dialogue.
Svrha ovoga rada bila je pridonijeti modelu pripreme učenika za aktivno argumentiranje u demokratskom društvu i naglasiti ulogu nastavnika u raspravama u učionici /1/. 245 studenata iznijelo je svoje mišljenje u Upitniku o dijalogu i argumentaciji. Cilj istraživanja bio je ispitati mišljenje studenata (budućih nastavnika) o argumentiranju. Rezultati pokazuju da studenti na pozitivniji način ocjenjuju područja argumentiranja u školi s aspekta odnosa između njezinih dionika, s tim da je najbolje ocijenjen odnos između učenika; oni koji imaju najviše znanja o konceptu argumentiranja pozitivno ocjenjuju to da uključivanje u različite aktivnosti u društvu razvija koheziju, dijalog i argumentiranje. Studenti s boljom procjenom važnih karakteristika nastavnika za argumentaciju pokazuju veće razumijevanje za poticanje školskih aktivnosti koje doprinose razvoju dijaloga.
Bibliografske bilješke na kraju teksta.
Abstract ; Sažetak.
Keywords: Aktivno građanstvo -- Argumentiranje -- Aktivno sudjelovanje -- Studenti